Wide-Gap Perovskite via Synergetic Surface Passivation and Its Application toward Efficient Stacked Tandem Photovoltaics - YAVUZ, İLHAN (WILEY-V C H VERLAG GMBH, 2022)
Superior bandgap tunability enables solution-processed halide perovskite a promising candidate for multi-junction photovoltaics (PVs). Particularly, optically coupling wide-gap perovskite by stacking with commercially available PVs such as silicon and CIGS (also known as 4-terminal tandem) simplifies the technology transfer process, and further advances the commercialization potential of perovskite technology. However, compared with matured PV materials and the phase-pure FAPbI(3), wide-gap perovskite still suffers from huge voltage deficits. Here, the authors take advantage of the synergetic effect behind a sequential fluoride and organic ammonium salt surface passivation strategy to control non-radiative energy losses, and obtained a 17.7% efficiency in infrared-transparent wide-gap perovskite solar cells (21.1% for opaque device), and achieved efficiencies of over 25% when stacked with commercial Si and CIGS products with original PCEs of 18-20% under a 4-terminal working condition.
Keywords: defect passivation; tandem structure; wide bandgap perovskites; SOLAR-CELLS; HIGH-PERFORMANCE